2011
DOI: 10.1002/jms.2018
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of relative LC/MS response of metabolites to parent drug in LC/nanospray ionization mass spectrometry: potential implications in MIST assessment

Abstract: There is an increasing demand for quantitative data on metabolite exposure triggered by regulatory guidances. This contribution describes the accuracy of nanoelectrospray ionization mass spectrometry response of drug compounds and their metabolites from biological matrices compared with radiometric quantification. This is a comprehensive investigation of a set of real-life pharmaceutical compounds in relevant matrices such as urine, bile, feces and plasma. The data suggest that nanoelectrospray mass spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Differences in ionization efficiency of compounds with different physicochemical characteristics are in general reduced by the application of chip-based NSI (Hop et al, 2005;Hop, 2006;Valaskovic et al, 2006;Wickremsinhe et al, 2006;Ramanathan et al, 2007). Recently, the accuracy of nano-electrospray ionization MS response of drug compounds and their respective metabolites from biological matrices compared with accurate radiometric quantification was evaluated, and it has been demonstrated that nanoelectrospray mass spectrometry can be used for semiquantitation of metabolites (Schadt et al, 2011). For LESA-MS, the accuracy of semiquantification results was expected to be even higher, because no chromatographic separation was used, and therefore different LC mobile phase compositions and matrix effects could not contribute to variations in MS response.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in ionization efficiency of compounds with different physicochemical characteristics are in general reduced by the application of chip-based NSI (Hop et al, 2005;Hop, 2006;Valaskovic et al, 2006;Wickremsinhe et al, 2006;Ramanathan et al, 2007). Recently, the accuracy of nano-electrospray ionization MS response of drug compounds and their respective metabolites from biological matrices compared with accurate radiometric quantification was evaluated, and it has been demonstrated that nanoelectrospray mass spectrometry can be used for semiquantitation of metabolites (Schadt et al, 2011). For LESA-MS, the accuracy of semiquantification results was expected to be even higher, because no chromatographic separation was used, and therefore different LC mobile phase compositions and matrix effects could not contribute to variations in MS response.…”
Section: Discussionmentioning
confidence: 99%
“…Bioanalysis (2014) 6 (6) sizes. This, once again, could be a result of different resolution of undetected matrix components present in the final extracts.…”
Section: Research Article | Danaceau Yu Chambers and Fountainmentioning
confidence: 99%
“…Schadt et al compared the accuracy of determining relative abundance of metabolites (as percentage of parent) by MS peak areas and by radioactivity. Their data indicated that for the majority of metabolites, determination of abundance of metabolites (as percentage of parent) by MS peak areas were within threefold from that determined by radioactivity [6]. Therefore, MS peak areas of metabolites can provide an initial estimation of their relative abundance (i.e., likely to be a major or a minor metabolite).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…The possible explanations of this observation could be: 1) Non-cytochrome P450-dependent drug metabolism may lead to an overestimation of glucuronidation rate for drugs that could be metabolized by non-P450 enzymes; 2) different ionization efficiency between acyl glucuronide isomers and parent drug. Ionization efficiency of parent drug and metabolites has been extensively studied (Schadt et al, 2011), revealing that the MS signal intensity could vary remarkably, especially in cases of substantial structural differences between the parent drug and the metabolites. It is thus possible that the glucuronidation rate could not be properly assessed in absence of an analytical standard.…”
Section: Fda 2008mentioning
confidence: 99%